Molecular Phylogenetic Relationships and Cultural Conditions of Calocybe indica (Plant Tissue Culture and Biotechnology, 2025)
Calocybe indica known as a milky white, indigenous and medicinally important edible mushroom. The cultural conditions, molecular identification, and phylogenetic relationships of selected strains of Calocybe indica were examined. The optimal temperature for mycelial development was found to be 30°C, whereas the lowest growth occurred at 15°C. The most favorable growth occurs at a pH of 5. Based on the growth characteristics of various culture media, potato dextrose agar proved to be the most advantageous, while Hennerberg and Czapek Dox media were less suitable. Molecular identification and the phylogenetic relationships of the chosen IUM strains of C. indica were examined through their ITS and RAPD analyses. The selected strains of C. indica had total sequence lengths of ITS1, ITS2, and 5.8S rDNA ranging from 570 to 620 bp. The sizes of the ITS1 and ITS2 regions vary among strains, with ITS2 showing greater variety than ITS1. All strains contained identical 5.8S rDNA sequences, according to sequencing analysis. Eleven out of the twenty arbitrary 10-base oligonucleotide primers utilized to amplify genomic DNA segments for the chosen C. indica strains were effective. RAPD-PCR resulted in distinct multiple products, demonstrating significant variability among the strains assessed. The quantity of amplified bands differed based on the primers utilized or the strains evaluated. The DNA polymorphisms displayed consistent traits in the replicated trials. Thus, it can be concluded that ITS sequencing and RAPD methods were effective in identifying the genetic diversity of the chosen strains of Calocybe indica.Plant Tissue Cult. & Biotech. 34(2): 205-216, 2024 (December)